Balloon dilatation for paediatric airway stenosis: Evidence from the UK Airway Intervention Registry. (20th February 2020) - Powell, Steven; Keltie, Kim; Burn, Julie; Cole, Helen; Donne, Adam; Morrison, Gavin; Stephenson, Kate; Daniel, Mat; Gupta, Sanjeev; Wyatt, Michelle; Patrick, Hannah; Sims, Andrew
Abstract: Objectives: To assess the safety and efficacy in routine clinical practice of balloon dilatation procedures in the treatment of paediatric airway stenosis. Design: Observational data collection in prospective online research database. Setting: Acute NHS Trusts with ENT department undertaking complex paediatric airway work. Participants: Children (<18) undergoing balloon dilatation treatment for airway stenosis. Main outcome measures: Airway diameter, complications, hospital resource usage. Results: Fifty‐nine patients had 133 balloon procedures during 128 visits to 10 hospitals. Sixty‐nine (52%) of balloon procedures were conducted with a tracheostomy. Intra‐operative Cotton‐Myer grade decreased in 43 (57%). The mean pre‐balloon subglottic diameter was 4.2 [95% CI: 3.8 to 4.5] mm, and its rate of increase was 0.8 [0.5 to 1.2] mm per year modelled on 30 patients' long‐term data. As the primary treatment of stenosis, the procedural success rate of balloon dilatation (n = 52) was 65% (22% with tracheostomy, 88% without tracheostomy), and 71% as an adjunct to open reconstructive surgery (n = 7). In the 64 hospital visits where a balloon procedure was conducted with a tracheostomy in place, only one in‐hospital complication (lower respiratory tract infection) occurred. For those without a tracheostomy in place, in‐hospital complications occurred in seven of 64 balloon hospital visits, all related to ongoing or worsening stenosis. Six out‐of‐hospital complications were deemed related to ongoing or worsening stenosis following the procedure, and two complications were a combination of lower respiratory infection and ongoing or worsening stenosis. Conclusions: Balloon dilation increases the size of the airway intraoperatively and is associated with long‐term increase in airway diameter. Safety outcomes mostly relate to ongoing or worsening stenosis and are more common in patients without a tracheostomy.